Synthesis and preclinical application of a Prussian blue-based dual fluorescent and magnetic contrast agent (CA) - Hegedűs, Nikolett (2023)
The aim of this study was to develop and characterize a Prussian Blue based biocompatible and chemically stable T1 magnetic resonance imaging (MRI) contrast agent with near infrared (NIR) optical contrast for preclinical application. The physical properties of the Prussian blue nanoparticles (PBNPs) (iron (II); iron (III);octadecacyanide) were characterized with dynamic light scattering (DLS), zeta potential measurement, atomic force microscopy (AFM), and transmission electron microscopy (TEM). In vitro contrast enhancement properties of PBNPs were determined by MRI. In vivo T1-weighted contrast of the prepared PBNPs was investigated by MRI and optical imaging modality after intravenous administration into NMRI-Foxn1 nu/nu mice. The biodistribution studies showed the presence of PBNPs predominantly in the cardiovascular system. Briefly, in this paper we show a novel approach for the synthesis of PBNPs with enhanced iron content for T1 MRI contrast. This newly synthetized PBNP platform could lead to a new diagnostic agent, replacing the currently used Gadolinium based substances.